ANÁLISIS DE VIABILIDAD PARA LA IMPLEMENTACIÓN DE UN SOFTWARE PARA EL CONTROL ADMINISTRATIVO DEL SINDICATO PROVINCIAL DE CHOFERES PROFESIONALES DE LOS RÍOS - Quimi Varas, Wilmer Daniel (2018)
Through the development of the system seeks to provide specific information, which is planned to deliver in real time keeping the database with accurate and updated information, currently the Provincial Union of Professional Drivers of Los Rios lacks a system that allows provide the information required by the partners of the aforementioned place, producing a disadvantage in the accuracy of the data. Traditionally, administrative control processes are carried out through books, which is not a common method at present, where processes are carried out by means of systems implemented by companies in order to facilitate the work and execute them in a reliable and feasible way. This system will have the control that is necessary for the corrective action of the same, both the organizations and the systems have a purpose fixed by the determinative decisions at the highest level, of execution. In order to solve that, the environment of the place where the system will be implemented must be analyzed, with what resource is counted and what is needed. Establish a team of "user, technical and maintenance personnel" who will participate in the system implementation process, giving responsibilities.